2023
DOI: 10.1177/00048674221144262
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of suicidal ideation severity among treatment-seeking young people with major depressive disorder: The role of state and trait anxiety

Abstract: Objective: Depression and suicidal ideation are closely intertwined. Yet, among young people with depression, the specific factors that contribute to changes in suicidal ideation over time are uncertain. Factors other than depressive symptom severity, such as comorbid psychopathology and personality traits, might be important contributors. Our aim was to identify contributors to fluctuations in suicidal ideation severity over a 12-week period in young people with major depressive disorder receiving cognitive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…A study recruited young people aged 15 to 25 years who received randomized controlled treatment for moderate to severe major depressive symptoms. The study found that higher trait anxiety predicted higher suicidal ideation (Moller et al, 2023). The findings showed that high trait anxiety might precede and prospectively affect the development of depression symptoms, thus providing some evidence for the predictive values of trait anxiety for the developmental trajectories of depression symptoms.…”
Section: Trait Anxietymentioning
confidence: 76%
See 1 more Smart Citation
“…A study recruited young people aged 15 to 25 years who received randomized controlled treatment for moderate to severe major depressive symptoms. The study found that higher trait anxiety predicted higher suicidal ideation (Moller et al, 2023). The findings showed that high trait anxiety might precede and prospectively affect the development of depression symptoms, thus providing some evidence for the predictive values of trait anxiety for the developmental trajectories of depression symptoms.…”
Section: Trait Anxietymentioning
confidence: 76%
“…Similarity with previous literature Consistent with the hypothesis, trait anxiety was a significant predictor of the trajectory of depression symptoms during the transition into early adolescence. Previous studies have supported the transdiagnostic risk factor for trait anxiety for the development of depression symptoms (Carmela et al, 2022;Malhi et al, 2021 b;Moller et al, 2023;Wang et al, 2019 a). For example, a study with 178 depressive patients revealed that higher trait anxiety was associated with slower recovery from depression after treatment (Min et al, 2012).…”
Section: Trait Anxiety As the Predictor For The Trajectories Of Depre...mentioning
confidence: 86%
“…In a longitudinal evaluation of loneliness and social anxiety, Lim et al (2016) reported that loneliness is predictive of future social anxiety, but conversely, early social anxiety is also an independent predictor of future loneliness (which was not seen for depression or paranoia). Given loneliness and anxiety both constitute concerning risks for poor health outcomes (i.e., cardiovascular disease, dementia, cognitive decline; National Academies of Sciences Engineering and Medicine, 2020) and suicide (Kealy et al, 2021;Moller et al, 2023), it is critical that future research adequately considers, and further disentangles, the discrete yet interconnected nature of loneliness and anxiety in men.…”
Section: Discussionmentioning
confidence: 99%